Hubungan Pola Koping Dengan Tingkat Kecemasan Siswa Kelas XII Yang Akan Mengahadapi Ujian Nasional Di SMA Muhammadiyah 1 Surakarta - Suryono, Imam Hakim (2016)
ABSTRACT RELATIONSHIP BETWEEN COPING SYSTEM AND ANXIETY LEVEL OF CLASS XII STUDENTS WHO WILL FACE NATIONAL EXAM AT SMA Background: National exam for most students is often perceived as a stressor that can cause anxiety. Anxiety is a signal warning of the danger and allows a person to take action to address the threat. To overcome these threats, the students use coping system to solve problems, cope with changes and threatening situation both cognitivy and behavioraly. Objective: To determine the relationship coping system and anxiety level class XII students who will face national exam at SMA Muhammadiyah 1 Surakarta. Methods: This study used observational analytic with cross sectional approach. Total observasional population were 226 students, and the number of sample were 58 respondents who met the inclusion criteria, by using purposive sampling technique. Data collection was done by filling the biodata of respondents, JCS questionnaire, and TMAS questionnaire. Data were analyzed by Rank Spearman test. Result: From the analysis of the data showed r -0.322 It Means that is more adaptive coping system score decreasingly anxious, and conversely the more maladaptive coping system score, the more anxious by the strength correlation is weak. P value 0,014 that means there is a significant correlation between coping system and anxiety level of class XII students who will face national exam at SMA Muhammadiyah 1 Surakarta. Conclusion: there is a relationship between coping system and anxiety level of class XII students who will face national exam at SMA Muhammadiyah 1 Surakarta. Keywords : National Exam, Coping System, Anxiety Level Medical Faculty of Muhammadiyah Surakarta University 1 Student of medical faculty Muhammadiyah Surakarta University 2 Lecture of medical faculty Muhammadiyah Surakarta University